Microsurgical basics and bypass techniques - Belykh, Evgenii G.; Martirosyan, Nikolay L.; Kalani, Yashar (Thieme, 2020)
"All neurosurgeons must undergo rigorous training in the laboratory and practice bypass techniques repetitively before performing microneurosurgery on a patient. Microsurgical Basics and Bypass Techniques by Evgenii Belykh, Nikolay Martirosyan, and M. Yashar S. Kalani is a comprehensive yet succinct manual on fundamental laboratory techniques rarely included in clinical textbooks. The resource simplifies repetitive microsurgical practice in the laboratory by providing a menu of diverse, progressively challenging exercises. Step-by-step instructions accompanied by easy-to-understand illustrations, expert commentary, and videos effectively bridge the gap between laboratory practice and operating room performance. The book starts with an opening chapter on four founding principles of microsurgical practice inherited from great thinkers and concludes with a chapter featuring cerebrovascular bypass cases. Chapters 2-8 offer a complete one-week curriculum, with a different lab exercise each day, focused on learning basic microsurgery skills"--